La figura del "tirso" come exemplum dell'opera d'arte. Riflessioni sul nesso arte-immaginazione in Baudelaire (Materiali di Estetica. Terza serie, 2017)
This paper aims to show how the Baudelaire’s prose poem The Thyrsus, in Paris Spleen, constitues the exemplary exhibition of the idea of art itself and of its ontological and epistemological statute, according to the theoretical Baudelairian perspective. From this point of view, the paper highlights two features playing a decisive role in aesthetical terms: on the one hand, the Baudelairian image of the “thyrsus” presents itself as an authentic “short-circuit” of the Apollonian logos and the Dionysian pathos (according to Nietzsche’s lexicon); on the other hand, the same image of the thyrsus is conceivable as a sort of “symbol” (or as a sort of “equivalent”) of that instance of creativity closely related to the Kantian notion of “free schematism”. Thus, the figure of the thyrsus exhibits in an exemplary way – showing it “in action” and putting it in front of our eyes – the same utopian instance of “liberation of the possible” that, again under the Baudelairian perspective, belongs to the faculty of imagination.